Penerapan GMP (Good Manufacturing Practices) Pada Tortilla Jarula di UMKM Putri Rinjani Kabupaten Lombok Tengah - Kurratul Aini; Muktasam Muktasam; Hayati Hayati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
The Indonesian people already have enough awareness about safe food and become a separate reference for the food industry to apply it so that the food they produce is safe, of good quality, and can be accepted by consumers. Food safety can be achieved by carrying out one of the efforts to implement Good Manufacturing Practices (GMP) as was done in the production of Tortilla Jarula (Corn Seaweed) at UMKM Putri Rinjani, Central Lombok Regency. The purpose of this study was to analyze the application of GMP in Tortilla Jarula at Putri Rinjani UMKM, Central Lombok Regency. The research was conducted by observation and interview methods. Data analysis with descriptive method. The test results for the level of implementation of GMP in Putri Rinjani UMKM are quite (moderate) with a score of 75.00 %. The lowest GMP aspect is buildings and facilities with a score of 44.44% at a low level.